2014
DOI: 10.1016/j.redox.2013.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-mimetic peptide CB3 lowers MAPKinase activity in the Zucker rat brain

Abstract: Diabetes is a high risk factor for dementia. High glucose may be a risk factor for dementia even among persons without diabetes, and in transgenic animals it has been shown to cause a potentiation of indices that are pre-symptomatic of Alzheimer's disease. To further elucidate the underlying mechanisms linking inflammatory events elicited in the brain during oxidative stress and diabetes, we monitored the activation of mitogen-activated kinsase (MAPKs), c-jun NH2-terminal kinase (JNK), p38 MAP kinases (p38MAPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…Accordingly, JNK blockage mediated the inhibition of IRS-1 serine phosphorylation in the liver of ZDF rats [48] and in human hepatic cells [9], which has been related to an improved insulin resistance. Moreover, in the brain of ZDF rats, JNK and p38 were suppressed by a peptide with anti-diabetic properties [47]. Interestingly, in our experimental conditions, p-ERK values remained increased in ZDF rats fed with cocoa, and we have previously shown that a cocoa extract enhanced p-ERK values in hepatic cells, which was associated to a protective effect against an induced oxidative stress [25].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Accordingly, JNK blockage mediated the inhibition of IRS-1 serine phosphorylation in the liver of ZDF rats [48] and in human hepatic cells [9], which has been related to an improved insulin resistance. Moreover, in the brain of ZDF rats, JNK and p38 were suppressed by a peptide with anti-diabetic properties [47]. Interestingly, in our experimental conditions, p-ERK values remained increased in ZDF rats fed with cocoa, and we have previously shown that a cocoa extract enhanced p-ERK values in hepatic cells, which was associated to a protective effect against an induced oxidative stress [25].…”
Section: Discussionmentioning
confidence: 48%
“…Indeed, MAPKs induce negative regulators of insulin sensitivity such as protein-tyrosine phosphatase-1B, p-Ser307-IRS-1 and p-(Ser636/ 639)-IRS-1 [10,11]. In concert with this, high phosphorylated levels of ERK, JNK and p38-MAPK have been demonstrated in ZDF rats [47,48]. In the current study, feeding ZDF animals with the cocoa-rich diet abolished the increased p-JNK and p38 values, although not for p-ERK levels.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, TXMs reversed the inhibitory effects of (S)NO on the Prx-Trx system, suggesting that TXMs may hold potential to improve pathological conditions related to SNO stress. However, TXMs also imitate the oxidoreductase activity of Trx, regulating oxidation (i.e., disulfide formation) of Trx substrate proteins [71,72]. Moreover, similar to NOS inhibitors and antioxidant therapies, TXMs can affect basal SNO (and oxidation) levels.…”
Section: Possible Approaches To Pharmacologically Modulate Formation mentioning
confidence: 99%
“…The RF model could effectively predict AD. TXNIP is an early response gene involved in neuronal apoptosis induced by high glucose and oxidative stress [14]. It mediates neuronal repair when transiently expressed [15,16].…”
Section: Discussionmentioning
confidence: 99%